Half American: the epic story of African Americans fighting World War II at home and abroad (Viking, an imprint of Penguin Random House LLC, Books on Tape, 2022)
. Winner of the 2023 Anisfield-Wolf Book Award in Nonfiction . A New York Times Notable Book . A Best Book of the Year from TIME , Publishers Weekly , Booklist , Washington Independent Review of Books , and more! The definitive history of World War II from the African American perspective, written by civil rights expert and Dartmouth history professor Matthew Delmont "Matthew F. Delmont's book is filled with compelling narratives that outline with nuance, rigor, and complexity how Black Americans fought for this country abroad while simultaneously fighting for their rights here in the​ United States. Half American belongs firmly within the canon of indispensable World War II books." -Clint Smith, #1 New York Times bestselling author of How the Word Is Passed- A Reckoning with the History of Slavery Across America Over one million Black men and women served in World War II. Black troops were at Normandy, Iwo Jima, and the Battle of the Bulge, serving in segregated units and performing unheralded but vital support jobs, only to be denied housing and educational opportunities on their return home. Without their crucial contributions to the war effort, the United States could not have won the war. And yet the stories of these Black veterans have long been ignored, cast aside in favor of the myth of the "Good War" fought by the "Greatest Generation." Half American is American history as you've likely never read it before. In these pages are stories of Black heroes such as Thurgood Marshall, the chief lawyer for the NAACP, who investigated and publicized violence against Black troops and veterans; Benjamin O. Davis, Jr., leader of the Tuskegee Airmen, who was at the forefront of the years-long fight to open the Air Force to Black pilots; Ella Baker, the civil rights leader who advocated on the home front for Black soldiers, veterans, and their families; James Thompson, the 26-year-old whose letter to a newspaper laying bare the hypocrisy of fighting against fascism abroad when racism still reigned at home set in motion the Double Victory campaign; and poet Langston Hughes, who worked as a war correspondent for the Black press. Their bravery and patriotism in the face of unfathomable racism is both inspiring and galvanizing. In a time when the questions World War II raised regarding race and democracy in America remain troublingly relevant and still unanswered, this meticulously researched retelling makes for urgently necessary reading.

The last to vanish: a novel (S&S/ Marysue Rucci Books, Marysue Rucci Books/Scribner, Simon & Schuster Audio, Marysue Rucci Books, Scribner, Audioworks, Simon & Schuster Audio, Wheeler Publishing, a part of Gale, a Cengage Company, 2023)
INSTANT NEW YORK TIMES BESTSELLER "This eerie thriller...can stand next to Shirley Jackson's The Haunting of Hill House and Stephen King's The Shining ." -- Booklist (starred review) New York Times bestselling author Megan Miranda returns with a gripping and propulsive thriller that opens with the disappearance of a journalist who is investigating a string of vanishings in the resort town of Cutter's Pass--will its dark secrets finally be revealed? Ten years ago, Abigail Lovett fell into a job she loves, managing The Passage Inn, a cozy, upscale resort nestled in the North Carolina mountain town of Cutter's Pass. Cutter's Pass is best known for its outdoor offerings--rafting and hiking, with access to the Appalachian trail by way of a gorgeous waterfall--and its mysterious history. As the book begins, the string of unsolved disappearances that has haunted the town is once again thrust into the spotlight when journalist Landon West, who was staying at the inn to investigate the story of the vanishing trail , then disappears himself. Abby has sometimes felt like an outsider within the community, but she's come to view Cutter's Pass as her home. When Landon's brother Trey shows up looking for answers, Abby can't help but feel the town closing ranks. And she's still on the outside. When she finds incriminating evidence that may bring them closer to the truth, Abby soon discovers how little she knows about her coworkers, neighbors, and even those closest to her. Megan Miranda brings her best writing to The Last to Vanish , a riveting thriller filled with taut suspense and shocking twists that will keep you guessing until the very end.

Screaming on the inside: the unsustainability of American motherhood (HarperCollins, HarperAudio, Harper Colins Publishers, Mariner Books, 2022)
"If this book feels like it's sounding the alarm on the state of American motherhood, well, that's because it is." -- San Francisco Chronicle In this timely and necessary book, New York Times opinion writer Jessica Grose dismantles two hundred years of unrealistic parenting expectations and empowers today's mothers to make choices that actually serve themselves, their children, and their communities Close your eyes and picture the perfect mother. She is usually blonde and thin. Her roots are never showing and she installed that gleaming kitchen backsplash herself (watch her TikTok for DIY tips). She seamlessly melds work, wellness and home; and during the depths of the pandemic, she also ran remote school and woke up at 5 a.m. to meditate. You may read this and think it's bananas; you have probably internalized much of it. Journalist Jessica Grose sure had. After she failed to meet every one of her own expectations for her first pregnancy, she devoted her career to revealing how morally bankrupt so many of these ideas and pressures are. Now, in Screaming on the Inside, Grose weaves together her personal journey with scientific, historical, and contemporary reporting to be the voice for American parents she wishes she'd had a decade ago. The truth is that parenting cannot follow a recipe; there's no foolproof set of rules that will result in a perfectly adjusted child. Every parent has different values, and we will have different ideas about how to pass those values along to our children. What successful parenting has in common, regardless of culture or community, is close observation of the kind of unique humans our children are. In thoughtful and revelatory chapters about pregnancy, identity, work, social media, and the crisis of the Covid-19 pandemic, Grose explains how we got to this moment, why the current state of expectations on mothers is wholly unsustainable, and how we can move towards something better.
How did we get here? , Pregnancy , Identity , Work , Social media , Everything falls apart , How do we make meaningful change?

Bittersweet: how sorrow and longing make us whole (Crown, Random House Large Print, Books on Tape, Random House Audio, 2023)
#1 NEW YORK TIMES BESTSELLER * OPRAH'S BOOK CLUB PICK * The author of the bestselling phenomenon Quiet explores the power of the bittersweet personality, revealing a misunderstood side of mental health and creativity while offering a roadmap to facing heartbreak in order to live life to the fullest. " Bittersweet has the power to transform the way you see your life and the world."--OPRAH "Grabs you by the heart and doesn't let go."--BRENÉ BROWN, author of Atlas of the Heart "Susan Cain has described and validated my existence once again!"--GLENNON DOYLE, author of Untamed "The perfect cure for toxic positivity."--ADAM GRANT, author of Think Again LONGLISTED FOR THE PORCHLIGHT BUSINESS BOOK AWARD * ONE OF THE BEST BOOKS OF THE YEAR: The Wall Street Journal, Mashable Bittersweetness is a tendency to states of longing, poignancy, and sorrow; an acute awareness of passing time; and a curiously piercing joy at the beauty of the world. It recognizes that light and dark, birth and death--bitter and sweet--are forever paired. If you've ever wondered why you like sad music . . . If you find comfort or inspiration in a rainy day . . . If you react intensely to music, art, nature, and beauty . . . Then you probably identify with the bittersweet state of mind. With Quiet, Susan Cain urged our society to cultivate space for the undervalued, indispensable introverts among us, thereby revealing an untapped power hidden in plain sight. Now she employs the same mix of research, storytelling, and memoir to explore why we experience sorrow and longing, and how embracing the bittersweetness at the heart of life is the true path to creativity, connection, and transcendence. Cain shows how a bittersweet state of mind is the quiet force that helps us transcend our personal and collective pain, whether from a death or breakup, addiction or illness. If we don't acknowledge our own heartache, she says, we can end up inflicting it on others via abuse, domination, or neglect. But if we realize that all humans know--or will know--loss and suffering, we can turn toward one another. At a time of profound discord and personal anxiety, Bittersweet brings us together in deep and unexpected ways.
Introduction: The power of bittersweet --, Part I. Sorrow and longing: how can we transform pain into creativity, transcendence, and love?. What is sadness good for? --, Why do we long for "perfect" and unconditional love? (And what does this have to do with our love of sad songs, rainy days, and even the divine?) --, Is creativity associated with sorrow, longing--and transcendence? --, How should we cope with lost love? --, Part II. Winners and losers: how can we live and work authentically in a "tyranny of positivity"?. How did a nation founded on so much heartache turn into a culture of normative smiles? --, How can we transcend enforced positivity in the workplace, and beyond? --, Part III. Mortality, impermanence, and grief: how should we live, knowing that we and everyone we love will die?. Should we try to live forever? --, Should we try to "get over" grief and impermanence? --, Do we inherit the pain of our parents and ancestors? And, if so, can we transform it generations later? --, Coda: How to go home --, A Book Club Guide.

The passenger (Passenger novels, 1, 1, 2023)
NEW YORK TIMES BEST SELLER * The first of a two-volume masterpiece, The Passenger series, from t he Pulitzer Prize-winning author of The Road * T he story of a salvage diver, haunted by loss, afraid of the watery deep, pursued for a conspiracy beyond his understanding, and longing for a death he cannot reconcile with God. A NEW YORK TIMES BEST BOOK OF THE YEAR "Blends the rowdy humor of some of McCarthy's early novels with the parched tone of his more apocalyptic later work." -- The New York Times Stella Maris , the second volume in The Passenger series, is available now. 1980, PASS CHRISTIAN, MISSISSIPPI: It is three in the morning when Bobby Western zips the jacket of his wet suit and plunges from the Coast Guard tender into darkness. His dive light illuminates the sunken jet, nine bodies still buckled in their seats, hair floating, eyes devoid of speculation. Missing from the crash site are the pilot's flight bag, the plane's black box, and the tenth passenger. But how? A collateral witness to machinations that can only bring him harm, Western is shadowed in body and spirit--by men with badges; by the ghost of his father, inventor of the bomb that melted glass and flesh in Hiroshima; and by his sister, the love and ruin of his soul. Traversing the American South, from the garrulous barrooms of New Orleans to an abandoned oil rig off the Florida coast, The Passenger is a breathtaking novel of morality and science, the legacy of sin, and the madness that is human consciousness.

The longest ride: a novel (Hachette Audio, Grand Central Publishing, a division of Hachette Book Group, Grand Central Publishing, 2015)
From the dark days of WWII to present-day North Carolina, this New York Times bestseller shares the lives of two couples overcoming destructive secrets -- and finding joy together. Ira Levinson is in trouble. Ninety-one years old and stranded and injured after a car crash, he struggles to retain consciousness until a blurry image materializes beside him: his beloved wife Ruth, who passed away nine years ago. Urging him to hang on, she forces him to remain alert by recounting the stories of their lifetime together - how they met, the precious paintings they collected together, the dark days of WWII and its effect on them and their families. Ira knows that Ruth can't possibly be in the car with him, but he clings to her words and his memories, reliving the sorrows and everyday joys that defined their marriage. A few miles away, at a local bull-riding event, a Wake Forest College senior's life is about to change. Recovering from a recent break-up, Sophia Danko meets a young cowboy named Luke, who bears little resemblance to the privileged frat boys she has encountered at school. Through Luke, Sophia is introduced to a world in which the stakes of survival and success, ruin and reward -- even life and death - loom large in everyday life. As she and Luke fall in love, Sophia finds herself imagining a future far removed from her plans -- a future that Luke has the power to rewrite . . . if the secret he's keeping doesn't destroy it first. Ira and Ruth. Sophia and Luke. Two couples who have little in common, and who are separated by years and experience. Yet their lives will converge with unexpected poignancy, reminding us all that even the most difficult decisions can yield extraordinary journeys: beyond despair, beyond death, to the farthest reaches of the human heart.

Amari and the night brothers (Amari, 1, 1, 2022)
New York Times bestseller! Artemis Fowl meets Men in Black in this exhilarating debut middle grade fantasy, the first in a series filled with #blackgirlmagic. Perfect for fans of Tristan Strong Punches a Hole in the Sky, the Percy Jackson series, and Nevermoor. Amari Peters has never stopped believing her missing brother, Quinton, is alive. Not even when the police told her otherwise, or when she got in trouble for standing up to bullies who said he was gone for good. So when she finds a ticking briefcase in his closet, containing a nomination for a summer tryout at the Bureau of Supernatural Affairs, she's certain the secretive organization holds the key to locating Quinton--if only she can wrap her head around the idea of magicians, fairies, aliens, and other supernatural creatures all being real. Now she must compete for a spot against kids who've known about magic their whole lives. No matter how hard she tries, Amari can't seem to escape their intense doubt and scrutiny--especially once her supernaturally enhanced talent is deemed "illegal." With an evil magician threatening the supernatural world, and her own classmates thinking she's an enemy, Amari has never felt more alone. But if she doesn't stick it out and pass the tryouts, she may never find out what happened to Quinton. Plus don't miss the thrilling sequel, Amari and the Great Game!

I found you: a novel (Dreamscape Media, Thorndike Press, a part of Gale, Cengage Learning, Atria Books, Dreamscape Media, LLC, Pocket Books, an imprint of Simon & Schuster, Inc, 2019)
"Readers of Liane Moriarty, Paula Hawkins, and Ruth Ware will love." -- Library Journal (starred review) "Jewell's novel explores the space between going missing and being lost....how the plots intersect and finally collide is one of the great thrills of reading Jewell's book. She ratchets up the tension masterfully, and her writing is lively." -- New York Times In the windswept British seaside town of Ridinghouse Bay, single mom Alice Lake finds a man sitting on a beach outside her house. He has no name, no jacket, and no idea how he got there. Against her better judgment, she invites him inside. Meanwhile, in a suburb of London, newlywed Lily Monrose grows anxious when her husband fails to return home from work one night. Soon, she receives even worse news: according to the police, the man she married never even existed. Twenty-three years earlier, Gray and Kirsty Ross are teenagers on a summer holiday with their parents. The annual trip to Ridinghouse Bay is uneventful, until an enigmatic young man starts paying extra attention to Kirsty. Something about him makes Gray uncomfortable--and it's not just because he's a protective older brother. Who is the man on the beach? Where is Lily's missing husband? And what ever happened to the man who made such a lasting and disturbing impression on Gray? "A mystery with substance" ( Kirkus Reviews ), I Found You is a delicious collision course of a novel, filled with the believable characters, stunning writing, and "surprising revelations all the way up to the ending" ( Booklist ) that make the New York Times bestselling author of Then She Was Gone Lisa Jewell so beloved by audiences on both sides of the Atlantic.

The poet X: A novel (HarperTeen, an imprint of HarperCollins Publishers, Thorndike Press, a part of Gale, a Cengage Company, Quill Tree Books, HarperCollins, Findaway World, LLC, HarperTeen, an imprint of HarperCollinsPublishers, Harper Audio, 2023)
Winner of the National Book Award for Young People's Literature, the Michael L. Printz Award, and the Pura Belpré Award! Fans of Jacqueline Woodson, Meg Medina, and Jason Reynolds will fall hard for this astonishing New York Times-bestselling novel-in-verse by an award-winning slam poet, about an Afro-Latina heroine who tells her story with blazing words and powerful truth. Xiomara Batista feels unheard and unable to hide in her Harlem neighborhood. Ever since her body grew into curves, she has learned to let her fists and her fierceness do the talking. But Xiomara has plenty she wants to say, and she pours all her frustration and passion onto the pages of a leather notebook, reciting the words to herself like prayers--especially after she catches feelings for a boy in her bio class named Aman, who her family can never know about. With Mami's determination to force her daughter to obey the laws of the church, Xiomara understands that her thoughts are best kept to herself. So when she is invited to join her school's slam poetry club, she doesn't know how she could ever attend without her mami finding out. But she still can't stop thinking about performing her poems. Because in the face of a world that may not want to hear her, Xiomara refuses to be silent. "Crackles with energy and snaps with authenticity and voice." --Justina Ireland, author of Dread Nation "An incredibly potent debut." --Jason Reynolds, author of the National Book Award Finalist Ghost "Acevedo has amplified the voices of girls en el barrio who are equal parts goddess, saint, warrior, and hero." --Ibi Zoboi, author of American Street
Part I. In the beginning was the word: Friday, August 24: Stoop-sitting ; Unhide-able ; Mira, muchacha ; Names ; The first words ; Mami works --, Tuesday, August 28: Confirmation class ; God ; "Mami," I say to her on the walk home ; When you're born to old parents ; When you're born to old parents, continued ; When you're born to old parents, continued again ; The last word on being born to old parents ; Rumor has it --, Tuesday, September 4: First confirmation class ; Father Sean ; Haiku ; Boys ; Caridad and I shouldn't be friends ; Questions I have --, Wednesday, September 5: Night before the first day of school --, Thursday, September 6: H.S ; Ms. Galiano ; Rough draft of assignment 1 : write about the most impactful day of your life ; Final draft of assignment 1 (what I actually turn in) ; The routine ; Altar boy ; Twin's name ; More about Twin --, Tuesday, September 11: It's only the first week of tenth grade ; How I feel about attention --, Saturday, September 15: Games ; After ; Okay? --, Sunday, September 16: On Sunday ; During communion ; Church mass ; Not even close to haikus ; Holy water ; People say ; On Papi ; All over a damn water --, Monday, September 17: The flyer ; After the buzz dies down --, Tuesday, September 18: Aman ; Whispering with Caridad later that day ; What Twin be knowing ; Sharing ; Questions for Ms. Galiano ; Spoken word ; Wait ; Holding a poem in your hand ; J. Cole vs. Kendrick Lamar ; Asylum ; What I tell Aman ; Dreaming of him tonight --, Thursday, September 20: The thing about dreams ; Date ; Mami's dating rules ; Clarification on dating rules --, Friday, September 21: Feeling myself., Part II. And the word was made flesh: Smoke parks ; I decided a long time ago ; Why Twin is a terrible twin ; Why Twin is a terrible twin, for real ; Why Twin is a terrible twin (last and most important reason) ; But why Twin is still the only boy I'll ever love --, Sunday, September 23: Communication ; About A --, Monday, September 24: Catching feelings ; Notes with Aman --, Tuesday, September 25: What I didn't say to Caridad in confirmation class Lectures ; Ms. Galiano's sticky note on top of assignment 1 ; Sometimes someone says something --, Friday, September 28: Listening ; Mother business And then he does ; Warmth --, Tuesday, October 9: The next couple of weeks ; Eve ; I think the story of Genesis is mad stupid ; As we are packing to leave ; Father Sean ; Answers ; Rough draft assignment 2 : last paragraphs of my biography ; Final draft of assignment 2 (What I actually turn in) ; Hands ; Fingers --, Tuesday, October 16: Talking church ; Swoon ; Telephone ; Over breakfast ; Angry cat, happy X --, Friday, October 19: About being in like ; Music --, Tuesday, October 23: Ring the alarm ; The day ; Wants ; At my train stop ; What I don't tell Aman ; Kiss stamps ; The last fifteen-year-old ; Concerns ; What Twin knows ; Hanging over my head --, Friday, October 26: Friday ; Black & blue ; Tight --, Saturday, October 27: Excuses ; Costume ready ; Reuben's house party ; One dance ; Stoop-sitting, with Aman ;, Convos with Caridad --, Sunday, October 28: Braiding --, Monday, October 29: Fights ; Scrapping ; What we don't say ; Gay ; Feeling off when Twin is mad ; Rough draft of assignment 3 : describe someone you consider misunderstood by society ; Final draft of assignment 3 (what I actually turn in) --, Wednesday, November 7: Announcements ; Ice-skating ; Until ; Love --, Thursday, November 8: Around and around we go ; After skating ; This body on fire ; The shit & the fan ; Miracles ; Fear ; Ants ; I am no ant ; Diplomas ; Cuero ; Mami says ; Repetition ; Another thing you think while your kneeling on rice that have nothing to do with repentance Things you think while your kneeling on rice that have nothing to do with repentance ; The last thing you think while your kneeling on rice that have nothing to do with repentance ; Leaving ; What do you need from me? ; Consequences ; Late that night --, Friday, November 9: In front of my locker., Part III. The voice of one crying in the wilderness: Silent world --, Sunday, November 11: Heavy ; My confession ; Father Sean says ; Prayers ; How I can tell ; Before we walk in the house ; My heart is a hand --, Wednesday, November 14: A poem Mami will never read ; In translation ; Heartbreak ; Reminders ; Writing ; What I'd like to tell Aman when he sends another apology message --, Wednesday, November 21: Favors ; Pulled back --, Thursday, November 22: On Thanksgiving ; Haiku : the best part about Thanksgiving was when Mami ; Rough draft of assignment 4 : when was the last time you felt free? ; Rough draft of assignment 4 : when was the last time you felt free? ; Rough draft of assignment 4 : when was the last time you felt free? ; Final draft of assignment 4 (what I actually turn in) ; Gone --, Monday, December 10: Zeros ; Possibilities ; Can't tell me nothing --, Tuesday, December 11: Isabelle ; First poetry club meeting ; Nerves ; When I'm done ; Compliments ; Caridad is standing outside the church ; Hope is a thing with wings --, Thursday, December 13: Here ; Haikus ; Offering ; Holding Twin ; Cody ; Problems ; Dominican Spanish lesson ; Permission --, Friday, December 14: Open mic night ; Signed up ; The mic is open ; Invitation --, Sunday, December 16: All the way hype --, Monday, December 17: At lunch on Monday --, Tuesday, December 18: At poetry club ; Every day after English class --, Monday, December 24: Christmas Eve ; It's a rosary --, Wednesday, December 26-Tuesday, January 1: Longest week --, Wednesday, January 2: The waiting game --, Tuesday, January 8: Birthdays ; The good ; The bad ; The ugly ; Let me explain ; If your hand causes you to sin ; Verses ; Burn ; Where there is smoke ; Things you think about in the split second your notebook is burning ; Other things you think about in the split second your notebook is burning ; My mother tries to grab me Returning ; On the walk to the train ; The ride ; No turning back ; Taking care ; In Aman's arms ; And I also know ; Tangled ; The next move ; there are words --, Wednesday, January 9: Facing it ; "You don't have to do anything you don't want to do" ; What I say to Ms. Galiano after she passes me a Kleenex; Going home ; Aman, Twin, and Caridad ; Divine intervention ; Homecoming ; My mother and I --, Thursday, January 24: Stronger ; Slam prep ; Ms. Galiano explains the five rules of slam ; Xiomara's secret rules of slam ; The poetry club's real rules of slam --, Friday, February 1: Poetic justice --, Friday, February 8: The aftermath of the slam ; At the New York citywide slam ; Celebrate with me ; Assignment 5 : first and final draft.

Don't breathe a word (HarperCollins, HarperTeen, HarperTeen, an imprint of HarperCollinsPublishers, 2021)
"A fast-paced, exhilarating story about a boarding school shrouded in secrecy and the girl who will do anything to right the institution's wrongs." --Jessica Goodman, Indiebound bestselling author of They Wish They Were Us Critically acclaimed author Jordyn Taylor weaves an addictive thriller perfect for fans of Truly Devious. Eva has never felt like she belonged . . . not in her own family or with her friends in New York City, and certainly not at a fancy boarding school like Hardwick Preparatory Academy. So, when she is invited to join the Fives, an elite secret society, she jumps at the opportunity to finally be a part of something. But what if the Fives are about more than just having the best parties and receiving special privileges from the school What if they are also responsible for keeping some of Hardwick's biggest secrets buried 1962: There is only one reason why Connie would volunteer to be one of the six students to participate in testing Hardwick's nuclear fallout shelter: Craig Allenby. While the thought of nuclear war sends her into a panic, she can't pass up the opportunity to spend four days locked in with the school's golden boy. However, Connie and the other students quickly discover that there is more to this "test" than they previously thought. As they are forced to follow an escalating series of commands, Connie realizes that one wrong move could have dangerous consequences. Separated by sixty years, Eva and Connie's stories become inextricably intertwined as Eva unravels the mystery of how six students went into the fallout shelter all those years ago . . . but only five came out.

I'm going to have a good day!: daily affirmations with Scarlett (Zonderkidz, 2023)
I am beautiful. I am kind. I am loved. In this uplifting picture book, young readers will discover how they can use daily affirmations to remind them of who they are and what makes them special. Join TikTok sensation Scarlett Gray and Tiania Haneline as they repeat exuberant affirmations that empower Scarlett throughout the day and inspire those around her to create their own uplifting self-talk. Every morning as her mom brushes her hair, Scarlett recites her daily affirmations. Those powerful words travel with her throughout her day, helping her replace negative thoughts with positive ones and live out the truth that she is beautiful, strong, brave, kind, and worthy of love. This fun-filled and inspiring kids' book also includes a list of uplifting and child-friendly statements your child can use to create their own daily affirmation routine. With fun illustrations from Stephanie Dehennin that make the story come alive, you and your young reader will discover how much words matter in your own lives. I'm Going to Have a Good Day! teaches children 4-8: how to incorporate positive affirmations into their lives that self-esteem is fun and empowering the benefits of passing on love and encouragement to others how to overcome negative thoughts in their everyday lives how to build confidence and see their self-worth I'm Going to Have a Good Day! is ideal for: birthday, Christmas, and holiday gifts bedtime and story time reading encouraging kindness and self-confidence sharing God's loves Build up your loved ones with encouraging words of affirmation, and they'll be saying, "I'm going to have a good day!"

How to start a fire: a novel (Wheeler Publishing, A part of Gale, Cengage Learning, Blackstone Publishing, Houghton Mifflin Harcourt, Blackstone Audio, Inc, HarperCollins, 2015)
" How to Start a Fire will keep you captivated from beginning to end."-- Town & Country "Excellent . . . Over the course of the novel we come to know intimately these three complicated women."-- Chicago Tribune "Whip smart and cunning, deeply funny and profoundly moving . . . A knockout."--Megan Abbott, author of The Fever When college roommates Anna and Kate find Georgiana Leoni passed out on a lawn, they wheel her to their dorm in a shopping cart. Twenty years later, they gather around a campfire at a New England mansion. What came between--the wild adventures, unspoken jealousies, and one night that changed everything--is the witty, poignant story of our strongest friendships, the people who know us better than we know ourselves. Anna is the de facto leader, as fearless as she is reckless. Quirky Kate is the loyal sidekick, until she's pushed too far. And stunning George is always desired, but just as frequently dumped. Alive with Lutz's crackling dialogue and propulsive storytelling, How to Start a Fire pulls us into the tangled bond shared by three intelligent, distinctive, and deeply real women and pays homage to the abiding, irrational love we have for the family we choose. "Lutz joins the ranks of authors who write deeply and sensitively about the shadowy yet life-affirming terrain of female friendship."-- Globe & Mail "Lutz hits a home run in this glorious exploration of friendship . . . [she] portrays three fully drawn, flawed, and compelling women with fresh insight into the mysterious terrain of female friendships--a mix of shared experiences, affection, empathy, jealousy, anger, and love."-- Publishers Weekly , starred review

How to excavate a heart (HarperTeen, an imprint of HarperCollins Publishers, Findaway World, LLC, HarperTeen, HarperCollins, 2023)
Stonewall Honor author Jake Maia Arlow delivers a sapphic Jewish twist on the classic Christmas rom-com in a read perfect for fans of Kelly Quindlen and Casey McQuiston. It all starts when Shani runs into May. Like, literally. With her mom's Subaru. Attempted vehicular manslaughter was not part of Shani's plan. She was supposed to be focusing on her monthlong paleoichthyology internship. She was going to spend all her time thinking about dead fish and not at all about how she was unceremoniously dumped days before winter break. It could be going better. But when a dog-walking gig puts her back in May's path, the fossils she's meant to be diligently studying are pushed to the side--along with the breakup. Then they're snowed in together on Christmas Eve. As things start to feel more serious, though, Shani's hurt over her ex-girlfriend's rejection comes rushing back. Is she ready to try a committed relationship again, or is she okay with this just being a passing winter fling?

Sunburn: a novel (HarperLuxe, an imprint of HarperCollinsPublishers, HarperCollins, HarperAudio, Findaway World, LLC, William Morrow, an imprint of HarperCollins Publishers, William Morrow, an imprint of HarperCollinsPublishers, Harper Audio, 2019)
Named one of the Most Anticipated Books of 2018 by Bustle, Popsugar, Wall Street Journal, Entertainment Weekly, Seattle Times, Book Riot, LitHub, BookPage, and Paperback Paris. "Every time Laura Lippman comes out with a new book, I get chills because I know I am back in the hands of the master. She is simply a brilliant novelist, an unflinching chronicler of life in America right now, and Sunburn is her dark, gleaming noir gem. Read it." -Gillian Flynn, #1 New York Times bestselling author of Gone Girl New York Times bestselling author Laura Lippman returns with a superb novel of psychological suspense about a pair of lovers with the best intentions and the worst luck: two people locked in a passionate yet uncompromising game of cat and mouse. But instead of rules, this game has dark secrets, forbidden desires, inevitable betrayals--and cold-blooded murder. One is playing a long game. But which one? They meet at a local tavern in the small town of Belleville, Delaware. Polly is set on heading west. Adam says he's also passing through. Yet she stays and he stays--drawn to this mysterious redhead whose quiet stillness both unnerves and excites him. Over the course of a punishing summer, Polly and Adam abandon themselves to a steamy, inexorable affair. Still, each holds something back from the other--dangerous, even lethal, secrets. Then someone dies. Was it an accident, or part of a plan? By now, Adam and Polly are so ensnared in each other's lives and lies that neither one knows how to get away--or even if they want to. Is their love strong enough to withstand the truth, or will it ultimately destroy them? Something--or someone--has to give. Which one will it be? Inspired by James M. Cain's masterpieces The Postman Always Rings Twice, Double Indemnity, and Mildred Pierce, Sunburn is a tantalizing modern noir from the incomparable Laura Lippman.

You don't have to say you love me: a memoir (Hachette Audio, Little, Brown and Company, Hachette Book Group, Findaway World, LLC, 2017)
A searing, deeply moving memoir about family, love, loss, and forgiveness from the critically acclaimed, bestselling National Book Award-winning author of The Absolutely True Diary of a Part-Time Indian . Family relationships are never simple. But Sherman Alexie's bond with his mother Lillian was more complex than most. She plunged her family into chaos with a drinking habit, but shed her addiction when it was on the brink of costing her everything. She survived a violent past, but created an elaborate facade to hide the truth. She selflessly cared for strangers, but was often incapable of showering her children with the affection that they so desperately craved. She wanted a better life for her son, but it was only by leaving her behind that he could hope to achieve it. It's these contradictions that made Lillian Alexie a beautiful, mercurial, abusive, intelligent, complicated, and very human woman. When she passed away, the incongruities that defined his mother shook Sherman and his remembrance of her. Grappling with the haunting ghosts of the past in the wake of loss, he responded the only way he knew how: he wrote. The result is a stunning memoir filled with raw, angry, funny, profane, tender memories of a childhood few can imagine, much less survive. An unflinching and unforgettable remembrance, You Don't Have to Say You Love Me is a powerful, deeply felt account of a complicated relationship.

This place is still beautiful (Balzer + Bray, an imprint of HarperCollins Publishers, Balzer + Bray, Findaway World, LLC, HarperCollins, 2022)
A sweeping debut novel about first love, complicated family dynamics, and the pernicious legacy of racism. Perfect for fans of Tahereh Mafi, Jandy Nelson, and Emily X.R. Pan, with crossover appeal for readers of Brit Bennett's The Vanishing Half and Celeste Ng's Everything I Never Told You. The Flanagan sisters are as different as they come. Seventeen-year-old Annalie is bubbly, sweet, and self-conscious, whereas nineteen-year-old Margaret is sharp and assertive. Margaret looks just like their mother, while Annalie passes for white and looks like the father who abandoned them years ago, leaving their Chinese immigrant mama to raise the girls alone in their small, predominantly white Midwestern town. When their house is vandalized with a shocking racial slur, Margaret rushes home from her summer internship in New York City. She expects outrage. Instead, her sister and mother would rather move on. Especially once Margaret's own investigation begins to make members of their community uncomfortable. For Annalie, this was meant to be a summer of new possibilities, and she resents her sister's sudden presence and insistence on drawing negative attention to their family. Meanwhile Margaret is infuriated with Annalie's passive acceptance of what happened. For Margaret, the summer couldn't possibly get worse, until she crosses paths with someone she swore she'd never see again: her first love, Rajiv Agarwal. As the sisters navigate this unexpected summer, an explosive secret threatens to break apart their relationship, once and for all. This Place Is Still Beautiful is a luminous, captivating story about identity, sisterhood, and how our hometowns are inextricably a part of who we are, even when we outgrow them.

Banyan Moon: a novel (Read with Jenna, ,, 2023)
A TODAY Show #ReadWithJenna Book Club Pick "A riveting mother-daughter tale." -- Elle "Radiant. ... An intimate account of one family's planting of roots in American soil and the sacrifices great and small that each member makes along the way." -- Washington Post A sweeping, evocative debut novel following three generations of Vietnamese American women reeling from the death of their matriarch, revealing the family's inherited burdens, buried secrets, and unlikely love stories. When Ann Tran gets the call that her fiercely beloved grandmother, Minh, has passed away, her life is already at a crossroads. In the years since she's last seen Minh, Ann has built a seemingly perfect life--a beautiful lake house, a charming professor boyfriend, and invites to elegant parties that bubble over with champagne and good taste--but it all crumbles with one positive pregnancy test. With both her relationship and carefully planned future now in question, Ann returns home to Florida to face her estranged mother, Huơng. Back in Florida, Huơng is simultaneously mourning her mother and resenting her for having the relationship with Ann that she never did. Then Ann and Huơng learn that Minh has left them both the Banyan House, the crumbling old manor that was Ann's childhood home, in all its strange, Gothic glory. Under the same roof for the first time in years, mother and daughter must face the simmering questions of their past and their uncertain futures, while trying to rebuild their relationship without the one person who's always held them together. Running parallel to this is Minh's story, as she goes from a lovestruck teenager living in the shadow of the Vietnam War to a determined young mother immigrating to America in search of a better life for her children. And when Ann makes a shocking discovery in the Banyan House's attic, long-buried secrets come to light as it becomes clear how decisions Minh made in her youth affected the rest of her life--and beyond. Spanning decades and continents, from 1960s Vietnam to the wild swamplands of the Florida coast, Banyan Moon is a stunning and deeply moving story of mothers and daughters, the things we inherit, and the lives we choose to make out of that inheritance.

One by one (Thorndike Press, a part of Gale, a Cengage Company, Encore, imprint of Simon & Schuster Audio, Simon & Schuster Audio, Pocket Books, Findaway World, LLC, Gallery/Scout Press, Scout Press, 2023)
"The Agatha Christie of our generation." --David Baldacci, #1 New York Times bestselling author "Diabolically clever." --Riley Sager, author of Final Girls The #1 New York Times bestselling author of The Turn of the Key and In a Dark, Dark Wood returns with another suspenseful thriller set on a snow-covered mountain. Getting snowed in at a luxurious, rustic ski chalet high in the French Alps doesn't sound like the worst problem in the world. Especially when there's a breathtaking vista, a full-service chef and housekeeper, a cozy fire to keep you warm, and others to keep you company. Unless that company happens to be eight coworkers...each with something to gain, something to lose, and something to hide. When the cofounder of Snoop, a trendy London-based tech startup, organizes a weeklong trip for the team in the French Alps, it starts out as a corporate retreat like any other: PowerPoint presentations and strategy sessions broken up by mandatory bonding on the slopes. But as soon as one shareholder upends the agenda by pushing a lucrative but contentious buyout offer, tensions simmer and loyalties are tested. The storm brewing inside the chalet is no match for the one outside, however, and a devastating avalanche leaves the group cut off from all access to the outside world. Even worse, one Snooper hadn't made it back from the slopes when the avalanche hit. As each hour passes without any sign of rescue, panic mounts, the chalet grows colder, and the group dwindles further...one by one.

The Black box: writing the race (Random House Large Print, Penguin Publishing Group, Penguin Press, 2024)
"Henry Louis Gates is a national treasure. Here, he returns with an intellectual and at times deeply personal meditation on the hard-fought evolution and the very meaning of African American identity, calling upon our country to transcend its manufactured divisions." -- Isabel Wilkerson, author of The Warmth of Other Suns and Caste "This is a literary history of Black America, but it is also an argument that African American history is inextricable from the history of African American literature." -- The New York Times A magnificent, foundational reckoning with how Black Americans have used the written word to define and redefine themselves, in resistance to the lies of racism and often in heated disagreement with each other, over the course of the country's history. Distilled over many years from Henry Louis Gates, Jr.'s legendary Harvard introductory course in African American Studies, The Black Box: Writing the Race , is the story of Black self-definition in America through the prism of the writers who have led the way. From Phillis Wheatley and Frederick Douglass, W.E.B. Du Bois and Booker T. Washington, to Zora Neale Hurston and Richard Wright, James Baldwin and Toni Morrison--these writers used words to create a livable world--a "home" --for Black people destined to live out their lives in a bitterly racist society. It is a book grounded in the beautiful irony that a community formed legally and conceptually by its oppressors to justify brutal sub-human bondage, transformed itself through the word into a community whose foundational definition was based on overcoming one of history's most pernicious lies. This collective act of resistance and transcendence is at the heart of its self-definition as a "community." Out of that contested ground has flowered a resilient, creative, powerful, diverse culture formed by people who have often disagreed markedly about what it means to be "Black," and about how best to shape a usable past out of the materials at hand to call into being a more just and equitable future. This is the epic story of how, through essays and speeches, novels, plays, and poems, a long line of creative thinkers has unveiled the contours of--and resisted confinement in--the "black box" inside which this "nation within a nation" has been assigned, willy nilly, from the nation's founding through to today. This is a book that records the compelling saga of the creation of a people.
The Black box , Race, reason, and writing , Who's your daddy? : Fredrick Douglass and the politics of self-representation , Who's your mama? : The politics of disrespectability , The "true art of a race's past" : Art propaganda, and the new negro , Modernism and its discontents : Zora Neale Hurston and Richard Wright play the dozens , Sellouts vs. race men : On the concept of passing , Conclusion : Policing the color line.

The friends we keep (Thorndike Press, a part of Gale, a Cengage Company, Findaway World, LLC, Berkley, an imprint of Penguin Random House LLC, Penguin Audio, Books on Tape, 2022)
As seen on The Today Show ! The Friends We Keep is the heartwarming and unforgettable New York Times bestselling novel from Jane Green, author of The Sunshine Sisters and The Beach House . Evvie, Maggie, and Topher have known one another since college. Their friendship was something they swore would last forever. Now years have passed, the friends have drifted apart, and they never found the lives they wanted--the lives they dreamed of when they were young and everything seemed possible. Evvie starved herself to become a supermodel but derailed her career by sleeping with a married man. Maggie married Ben, the boy she fell in love with in college, never imagining the heartbreak his drinking would cause. Topher became a successful actor, but the shame of a childhood secret shut him off from real intimacy. By their thirtieth reunion, these old friends have lost touch with one another and with the people they dreamed of becoming. Together again, they have a second chance at happiness...until a dark secret is revealed that changes everything. The Friends We Keep is about how despite disappointments we've had or mistakes we've made, it's never too late to find a place to call home.